2013
DOI: 10.3846/16111699.2012.720598
|View full text |Cite
|
Sign up to set email alerts
|

Examining What Best Explains Corporate Credit Risk: Accounting-Based Versus Market-Based Models

Abstract: This paper uses a sample of 2,186 credit default swap spreads quoted in the European market during the period 2002–2009 to empirically analyze which model – accounting- or market-based – better explains corporate credit risk. We find little difference in the explanatory power of these two approaches. Our results indicate that a comprehensive model that combines accounting- and market-based variables is the best option to explain the credit risk, suggesting that both types of data are complementary. We also dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Later on, researchers including Chava and Jarrow (2004) and Agarwal and Taffler (2008) articulated that market-based variables reflecting both internal and external information increase the overall predictability of distress prediction models. Further, Trujillo-Ponce et al (2014) suggested that a combined model with both accounting and market-based variables is the best option, as both types of information are important for distress prediction.…”
Section: Traditional Distress Prediction Modelsmentioning
confidence: 99%
“…Later on, researchers including Chava and Jarrow (2004) and Agarwal and Taffler (2008) articulated that market-based variables reflecting both internal and external information increase the overall predictability of distress prediction models. Further, Trujillo-Ponce et al (2014) suggested that a combined model with both accounting and market-based variables is the best option, as both types of information are important for distress prediction.…”
Section: Traditional Distress Prediction Modelsmentioning
confidence: 99%
“…Trujillo -Ponce et al (2014) showed that the comprehensive model, including market-based and accounting-based factors, was the most reliable model for predicting financial distress, compared with the Z-core and KMV-Merton model. Using 2186 credit default swaps (CDS) for the European market in both the pre-GFC (2002)(2003)(2004)(2005)(2006) and GFC (2007GFC ( -2009 periods, the comprehensive model was used to forecast the default probability in the volatile periods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several variations and extensions have been made to this basic model. Some of these are: Black and Cox (1976) [8]; Longstaff and Schwartz (1995) [9]; Brockman and Turtle (2003) [10]; Bandopadhyay (2007) [11]; Baninoe (2010) [12]; Laitinen (2010) [13]; Antonio et al (2012) [14]; and Kumar and Kumar (2012) [15]. Jensen and Meckling (1976) [16] and Vishny (1986, 1997) [17] conducted research on the impact of ownership patterns on default.…”
Section: Review Of Literaturementioning
confidence: 99%